INTELLECTUAL CAPITAL OF SOCIO-ECONOMIC REGION: MEASUREMENT AND STRUCTURE - Jan Ostoj (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2017)
This work is the first out of the series of three papers devoted to the estimation of value of intellectual capital of a given socio-economic area: voivodeship, municipality, country, region, etc. The concept of this estimation is based on the assumption that value of any socio-economic region, for its residents, is the amount of income that can be gained by locating their activities in the area they live. The layout of the presented method makes it possible to estimate all elements of intellectual capital, regardless of whether or not we are aware of their existence. In this paper, for the sake of estimation, definitional problems of the concept of intellectual capital are solved and the method which can estimate area value for its residents is proposed in order to derive a method for estimating intellectual capital of a given area as well as of each and every voivodship in Poland.